Core–shell CdS:Ga–ZnTe:Sb p–n nano-heterojunctions: fabrication and optoelectronic characteristics. Issue 12 (12th February 2015) - Wang, Li; Song, Hong-Wei; Liu, Zhen-Xing; Ma, Xu; Chen, Ran; Yu, Yong-Qiang; Wu, Chun-Yan; Hu, Ji-Gang; Zhang, Yan; Li, Qiang; Luo, Lin-Bao
Abstract : Thermal evaporation was developed to fabricate Ga doped CdS core–Sb doped ZnTe shell p–n nano-heterojunctions, which exhibit obvious sensitivity to 638 nm illumination, with a responsivity and a detectivity of 1.55 × 10 3 A W −1 and 8.7 × 10 13 cm Hz 1/2 W −1, respectively. Abstract : In this study, we reported on the construction of p–n junctions based on crystalline Ga-doped CdS–polycrystalline ZnTe nanostructures (NSs) for optoelectronic device application. The coaxial nano-heterojunction was fabricated by a two-step growth method. It is found that the absorption edge of CdS:Ga–ZnTe:Sb core–shell NSs red shifted to about 580 nm, compared with CdS nanowires (520 nm). The as-fabricated core–shell p–n junction exhibited obvious rectification characteristics with a low turn-on voltage of ∼0.25 V. What is more, it showed stable and repeatable photoresponse to 638 nm light illumination, with a responsivity and a detectivity of 1.55 × 10 3 A W −1 and 8.7 × 10 13 cm Hz 1/2 W −1, respectively, much higher than other photodetectors with similar device configurations. The generality of this study suggests that the present coaxial CdS:Ga–ZnTe:Sb core–shell nano-heterojunction will have great potential applications in future nano-optoelectronic devices.